Guinea : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Guinea during 1990-95. In 1995, expectations arising from the new discoveries of sizable oil reserves and double-digit growth in the non-oil economy-led by the timber industry-dominated economic developments. However, the fiscal position was again expansionary, as the fiscal deficit grew to 5 percent of GDP, exacerbating imbalances and adding to external payments arrears. Total budgetary revenue as a share of GDP fell and noninterest expenditure increased sharply including unclassified spending on the order of 3 percent of GDP.